Balanced Residential Conversion Fund in Achieving Justice and Prosperity - Ignatius Pradipa Probondaru; Dyah Setyorini; Endang Pandamdari (POLICY, LAW, NOTARY AND REGULATORY ISSUES, 2025)
The need for decent and affordable housing in Indonesia is becoming increasingly urgent alongside population growth and urbanization, but is hindered by high property prices and income inequality. This study aims to describe how Balanced Residential conversion funds contribute to achieving justice and welfare. This research uses a normative juridical method to analyze the Balanced Residential Conversion Fund policy as a solution to housing provision imbalances. The research focuses on implementation issues of Balanced Residential, including land price constraints, lack of developer incentives, and unclear fund conversion mechanisms. The results show that the Balanced Residential Conversion Fund policy, regulated through Government Regulations and managed by BP3, provides flexibility for developers while ensuring housing availability for low-income communities. However, three main challenges are identified: (1) absence of clear standards in calculating conversion fund amounts, (2) weak supervision of fund allocation, and (3) inaccurate mapping of housing needs. The research concludes that this policy has the potential to achieve social justice if improved through: (1) establishing transparent formulas for calculating conversion funds, (2) strengthening fund management and accountability systems, and (3) data-based mapping to ensure strategic locations for subsidized housing. With these improvements, Balanced Residential Conversion Funds can become an effective instrument in reducing housing backlog and creating social balance.